2021
DOI: 10.1186/s13073-021-00892-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogroup stability contrasts with high within sequence type complex dynamics of Escherichia coli bloodstream infection isolates over a 12-year period

Abstract: Background Escherichia coli is the leading cause of bloodstream infections, associated with a significant mortality. Recent genomic analyses revealed that few clonal lineages are involved in bloodstream infections and captured the emergence of some of them. However, data on within sequence type (ST) population genetic structure evolution are rare. Methods We compared whole genome sequences of 912 E. coli isolates responsible for bloodstream infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 81 publications
2
54
0
Order By: Relevance
“…With a curated data set of 5,653 E. coli genomes, we attempted to identify and understand the involvement of different genomic features with a plausible role in the evolution of 19 different ST lineages with varied pathogenic, resistance, and fitness capabilities, some bearing high risk of transmission with pandemic potentials. ST10 from our study has shown a wide serotype diversity, wherein its 1,036 genomes belonged to 222 serotypes; this is in agreement with a previous report ( 32 ). While a majority of the sequence types revealed a very high antigenic diversity, a few STs, such as ST131, ST11, ST405, and ST127, showed limited antigenic diversity where more than 80% of the genomes belonging to these STs represented a single serotype.…”
Section: Discussionsupporting
confidence: 93%
“…With a curated data set of 5,653 E. coli genomes, we attempted to identify and understand the involvement of different genomic features with a plausible role in the evolution of 19 different ST lineages with varied pathogenic, resistance, and fitness capabilities, some bearing high risk of transmission with pandemic potentials. ST10 from our study has shown a wide serotype diversity, wherein its 1,036 genomes belonged to 222 serotypes; this is in agreement with a previous report ( 32 ). While a majority of the sequence types revealed a very high antigenic diversity, a few STs, such as ST131, ST11, ST405, and ST127, showed limited antigenic diversity where more than 80% of the genomes belonging to these STs represented a single serotype.…”
Section: Discussionsupporting
confidence: 93%
“…STc155 strains are considered of animal origin with an evolution from wild type strains, becoming progressively resistant and, in many cases, later acquiring virulence genes (Skurnik et al, 2016). Indeed, in recent years multi-drug resistant (MDR) STc155 strains have been isolated with increasing frequency from extra-intestinal infections in humans (Royer et al, 2021). In our study STc155 isolates carried only a limited number of virulence genes but had already acquired an MDR profile.…”
Section: Discussionmentioning
confidence: 78%
“…The major question remaining is whether most ST58 from human faeces and ExPEC belong to the BAP2 cluster. Though not included in our study collection, ST58 sepsis isolates from multiple hospitals in Paris predominantly display O8/O9:H25 serotypes, as well as ColV and HPI marker genes, all of which were typical of BAP2 ST58 3 . In conjunction with our data, this tends to suggest that most ST58 ExPEC will belong to this cluster, however, an expanded dataset with more commensal and pathogenic human sequences would increase our confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Most ExPEC strains, including those in the globally dominant ST131 clonal group, are members of phylogroup B2 2 . The emergence of ST58 is perhaps best highlighted by a recent study that found the proportion of B1-ST58 isolated from bloodstream infections in the Paris region has more than doubled over a 12 year period in contrast to stable proportions of infections caused by phylogroup B2 isolates 3 . Beyond this study, E. coli ST58 is increasingly responsible for both sporadic and persistent cases of bloodstream infections in humans across the globe 4 12 .…”
Section: Introductionmentioning
confidence: 99%